28.2k views
5 votes
Given that f ′′ ( x ) = cos ( x ) f ″ ( x ) = cos ⁡ ( x ) , f ′ ( π / 2 ) = 7 f ′ ( π / 2 ) = 7 and f ( π / 2 ) = 5 f ( π / 2 ) = 5 find: f ′ ( x ) = f ′ ( x ) = f ( x ) = f ( x ) =

User Tiff
by
5.0k points

1 Answer

3 votes

Answer:
\sin x+6


-\cos x+6x+5-3\pi

Explanation:

Given


f''(x)=\cos x

Integrating the equation


\Rightarrow f''(x)=(d^2y)/(dx^2)=\cos x\\\\\Rightarrow \int \frac{\mathrm{d^2} y}{\mathrm{d} x^2}=\int \cos x\\\\\Rightarrow \frac{\mathrm{d} y}{\mathrm{d} x}=\sin x+c

Put
x=(\pi)/(2)\ \text{and}\ (dy)/(dx)=7


\Rightarrow 7=\sin (\pi )/(2)+c\\\Rightarrow c=7-1\\\Rightarrow c=6


\Rightarrow (dy)/(dx)=\sin x+6

again integrating both sides of the equation


\Rightarrow \int \frac{\mathrm{d} y}{\mathrm{d} x}=\int (\sin x+6)dx\\\\\Rightarrow y=-\cos x+6x+c_1

Put
x=(\pi)/(2)\ \text{and}\ y=5


\Rightarrow 5=-\cos (\pi)/(2)+6((\pi)/(2))+c_1\\\Rightarrow c_1=5-3\pi


\therefore f(x)=y=-\cos x+6x+5-3\pi

User Sickelap
by
5.6k points